Vulnerability and the discourse of 'forgotten people': populism, population and cultural change. Issue 5 (2nd September 2020) - Cover, Rob
ABSTRACT: Contemporary populist political rhetoric often makes use of a concept of a 'forgotten people' or a 'silent majority', who are constructed as a subset of population and often utilized as an electoral base by populist leaders, particularly in Australia, the United Kingdom and the United States of America. The concept emerged in the Twentieth Century and has undergone substantial re-configuration alongside other cultural emerges of the past fifty years. Among them is the re-configuration of the 'forgotten people' from being positioned to perceive themselves as a stoic, hard-working, domestic and normative middle-class to a group figured through a racial or ethnic 'authenticity' yet called upon to perceive themselves as vulnerable, precarious and at risk to both intellectual elites and marginalized groups including particularly migrants. Using cultural studies approaches, this paper examines some of those shifts in Australian and United States political discourse, how the concept of vulnerability is imputed for political ends, and the value of a more nuanced investigation of the affectively felt attachment to populist discourse among supporters as a form of identity practice. The paper aims to provide a more nuanced framework for scholarly understanding of, and intervention in, contemporary western populism.